The psychosocial impact of handicapped children on their siblings: A comparative study (Revista Puertorriqueña de Psicologia, 2016)
The psychosocial impact that a group of mentally retarded (MR) children had on their siblings was evaluated. The impact was assessed through the following instuments: Piers-Harris Children's Self Concept Scale (PH), Child Behavior Checklist (CBCL) and the Roca's Siblings' Relationship Scales (RSRS). The sample included 44 children of both sexes, ages 11-16, with intact families from middle/upper-middle class, who where older siblings to either an MR child (experimental group) or a nonretarded child (comparison group). No significant differences were found between the groups on the PH or on the Behavior Problems and Social Competence scales of the CBCL. Siblings of MR children were significantly closer to their MR sibling than controls as measured by the RSRS. It was concluded that siblings of MR children in the sample were not adversely affected by their respective MR brother or sister.